SEMANGAT MENUNTUT ILMU UNTUK MERAIH MARTABAT MULIA - Della Latifah Amanda; Nanda Ayuningtias (Pusat Riset dan Inovasi Nasional, 2023)
Knowledge is something that is very urgent in human life, in human life everyone needs knowledge. Islam is a perfect religion based on Quran and hadith. Islam places great emphasis on the obligation to seek knowledge, even the first verse that comes out is a verse about education. Because of the urgency of knowledge for humans, knowledgeable people are distinguished from people who are not knowledgeable. Knowledge is the key to happiness in this world and in the hereafter, if humans want to please Allah, humans must worship, carry out His commands and stay away from His prohibitions, must also use knowledge. Islam orders people to seek knowledge not only at school, but Islam teaches lifelong learning. The purpose of this writing is to discuss studying knowledge to achieve noble dignity. This research method uses a qualitative type through literature study and content analysis. The results and discussion of this study include an explanation of studying in Qs. Abasa (80):1-10 and Qs. Al-Mujadilah (58): 11 and the concept of knowledge in Islam. This study concludes that seeking knowledge is one of the most important parts of human life, without knowledge humans cannot develop. The search for knowledge is also considered as the starting point in attitude awareness. Seeking knowledge is obligatory for every Muslim man and woman. When Allah has sent down a mandatory order for something, then we must obey it.